Multiplasmids in Pseudomonas syringae pv. morsprunorum race 1 - Marasas, Carissa N.(Carissa Nalette) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1991.